Association between oxidative balance score and prevalence rates of thyroid dysfunction and autoimmune thyroiditis among U.S. adults: evidence from epidemiological studies - Wu, Jie; Dong, Xuqin; Yang, Qingkai; Niu, Junxian; Jia, Chuyu; Li, Xin; Li, Zhuyan (Frontiers in Nutrition, 2025)
BackgroundOxidative stress can impact the synthesis, metabolism, and signaling pathways of thyroid hormones. The Oxidative balance score (OBS) is an indicator used to measure an individual’s oxidative stress status by assessing the levels of oxidative and antioxidant substances in diet and lifestyle factors. This study aimed to explore the relationship between OBS and the prevalence of thyroid dysfunction.MethodsThis study investigated the relationship between OBS and the prevalence of thyroid dysfunction using data from 6,268 participants in the 2007–2012 National Health and Nutrition Examination Survey (NHANES). Weighted multivariate logistic regression and restricted cubic spline (RCS) regression were employed to analyze this association, assessing both linear and potential non-linear relationships.ResultsAfter adjusting for covariates, our research revealed that the prevalence of subclinical hyperthyroidism (SCHyper) decreased by 7.4% for each additional OBS unit[OR = 0.926, 95% CI = (0.884, 0.971), p = 0.002]. When the OBS was categorized, we also discovered that individuals with the highest OBS exhibited a 62.3% reduced risk of developing SCHyper in comparison to those with the lowest OBS. Similarly to OBS, the prevalence of SCHyper diminished by 7.7% for every extra unit of OBS added to the diet [OR = 0.923, 95% CI = (0.874, 0.974), p = 0.005]. A stratified analysis revealed that the protective effect of OBS against SCHyper was particularly strong in women, non-Hispanic White people, individuals with poverty to income ratio (PIR) greater than 3.5, and those with a Urinary iodine concentration (UIC) below 300 ug/L (all P for interaction < 0.05). Additionally, our investigation revealed a U-shaped curve relationship between OBS and SCHyper.ConclusionResearch indicates a negative correlation between OBS and the risk of SCHyper, suggesting that a higher intake of antioxidants and reduced exposure to pro-oxidants may help lower the risk of SCHyper. These results offer new insights into the prevention and treatment of patients with SCHyper.